Strategi Kepala Sekolah dalam Meningkatkan Mutu Pembelajaran Pendidikan Agama Islam di Madrasah Ibtidaiyah Swasta Al-Hikmah Kecamatan Beringin Deli Serdang - Neliwati; Siti Aisyah; Abdullah Fikri Sholehuddin SN; Robbirham (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to identify and analyze the strategies implemented by school principals to improve the quality of Islamic Religious Education (PAI) learning at Al-Hikmah Private Elementary School, Beringin District, Deli Serdang. The method used is qualitative descriptive, with data collection techniques including interviews, observations, and documentation. Data analysis is conducted through data reduction, data presentation, and conclusion drawing. Data validity is tested using method triangulation. The results of the study indicate that the principal applies various strategies, such as enhancing teacher competence through training and workshops, as well as implementing effective interactive learning methods. Despite challenges such as limited resources and resistance to change, these efforts have resulted in a significant improvement in the quality of PAI learning. In conclusion, the principal plays a crucial role in improving educational quality through appropriate strategies, which are vital for achieving optimal educational goals and making a positive contribution to society.